x²+4x+3=0
(x+1)(x+3) = 0
x' = -1 ..... or ...... x'' = -3
₢
2006-12-04 05:12:32
·
answer #1
·
answered by Luiz S 7
·
0⤊
0⤋
Technically, the answer is "it's a polynomial equation". But I think you are looking for what possible values of x would satisfy that equation.
The general strategy here is to factor the equation such that the two factors multiplied against each other equals 0. Once this is the case, and we know that something times 0 equals 0, we would know that one (or both) of the factors equal 0 and therefore can solve for each case.
x^2 + 4x + 3 = 0
Factoring this you get:
(x + 3)(x + 1) = 0
You probably remember learning about the FOIL method (first, outside, inside, last). Factoring is essentially the FOIL method backwards.
Knowing that one of the two factors needs to equal 0 in order for the product to equal 0, let's set each one equal to zero.
x + 3 = 0
therefore, x = -3
x + 1 = 0
therefore, x = -1
The beauty of math is you can (and should) double check your answer! Set x = -1 in the original problem to see if it works:
(-1)^2 + 4(-1) + 3 = 0?
1 - 4 + 3 = 0? Yes, therefore correct!
Now set x = -3 in the original problem:
(-3)^2 + 4(-3) + 3 = 0?
9 - 12 + 3 = 0? Yes, therefore correct!
So you have now confirmed the two answers (x = -1, x = -3) are correct.
2006-12-04 13:02:21
·
answer #2
·
answered by sep_n 3
·
2⤊
0⤋
1 x 3 = 3
1 + 3 = 4
So, you can do this:
x^2 + x +3 x + 3 = x (x+1) + 3 (x+1) = (x+1)(x+3)
So, if you want to solve (x+1)(x+4) = 0, and if you recall that x + 1 and x + 4 are numbers, when you plug a real number there, then you will notice that their product can only be 0 when one of them is 0.
You have then 2 possibilities:
x + 1 = 0, hence x = -1
or
x + 3 = 0, hence x = -3
Ana
2006-12-04 13:20:55
·
answer #3
·
answered by MathTutor 6
·
0⤊
0⤋
x^2 + 4x + 3 = 0
(x + 3)(x + 1) = 0
x + 3 = 0 or x + 1 = 0
x = -3 or x = -1
QED
2006-12-04 12:53:37
·
answer #4
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
It's a quadratic equation.
I'm surprised that you don't appear to be interested in its solution. The LHS is in fact trivial to factorize; so that:
(x + 1)(x + 3) = 0.
So the solutions are x = -1 or x = - 3.
(Check this out; could you really not have done this?)
Live long and prosper.
2006-12-04 12:58:32
·
answer #5
·
answered by Dr Spock 6
·
0⤊
0⤋
x = -0.5
x = -3
Thats right
2006-12-04 14:34:46
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋